Funkcja politycznych słów kluczy w memach internetowych - Niekrewicz, Agnieszka A. (Forum Lingwistyczne, 2020)
The subject of the study is the role of political key words used in memes. To determine their role, a semantic and stylistic analysis of Polish-language memetic statements from 2012–2019 was used, in which the following words were included: sorrel, mirabelles, trotyl, octopuses, light bulb, salad. The article shows that the use of key words even in a completely neutral context allows us to activate references to negatively evaluated events and situations, and to recall the emotions and views associated with them. In addition, quoting chronologically diverse examples of the use of key words has lead to the possibility of recreating the process of extending their meanings, which is the result of releasing quotes associated with a specific situation from their function.